Perbaikan Penampilan Produksi Ayam Pedaging dengan Penambahan Ekstraksi Temulawak Pelarut Ethanol - Agung Adi Candra; Dwi Desmiyeni Putri; Zairiful Zairiful (Politeknik Negeri Lampung., 2014)
Broiler is been developed anymal as a source of animal protein needs. Various feed additif given to broiler to spur additional growth as well as feed and medicine. One of the diseases that are immunosuppressed chickens is coccidiosis. Chickens infected with coccidiosis will show symptoms of diarrhea, emaciation and intestinal damage simultaneously, thus reducing the rate of growth in chickens. With the ability of anti-diarrhea and anti-inflammatory turmeric is expected to be an alternative for the treatment and prevention of coccidiosis in particular and general gastrointestinal disease in chickens. The purpose of this study was to determine the activity of ginger are extracted with solvent water to the broiler performance infected by Eimeria maxima. The results showed that administration of turmeric extraction with ethanol can increase body weight gain, feed efficiency and lower feed conversion value is better than giving solvent extraction of turmeric with water. turmeric extraction with ethanol was not effect to blood diferentiation but decrease level of total cholesterol, trigliserida, HDL, dan LDL on serum Keywords: performance, broiler, Eimeria maxima, turmeric